Maastricht 30: A Central European Perspective (Studies of the Central European Professors’ Network, 2025)
The book addressed topics related to the political discourse the time the Maastricht Treaty was signed, when the ‘heightened atmosphere’ attributable to the successful recovery from the Eurosclerosis and the dissolution of the Soviet Union – which made further enlargement possible –, two objectives have become the fundamental guiding principles at EU level: the continued internal deepening of integration – in other words an ‘ever closer union’ and the continued geographical enlargement. The above mentioned five topics, which the contributors of this book elaborate on are as follows: (i) constitutional identity versus ‘ever closer union’; (ii) institutional reforms in connection with the Future of Europe conference, (iii) the future of the Economic and Monetary Union, (iv) the dilemmas of geographical expansion – that is where are the final geopolitical boundaries of EU enlargement – and last, but not least (v) the evaluation of the Union’s energy policy. Only few of the goals set at the ‘Maastricht era’ have been realised in the form envisaged by the decision makers of the time: the political realities of the past thirty years have largely overridden the then euphoric mood. It is therefore necessary to draw the conclusions from these lessons to decide on the objectives for the next thirty years. The editors invite the reader to draw these conclusions based on the chapters of the book, which provide an insight into the above five topics either retrospectively or with a view to the future.